Genetic analysis of resistance to maize lethal necrosis with emphasis on strategies for improvement of host resistance - Kwemoi, Daniel Bomet (University of the Free State, 2021)
Maize lethal necrosis (MLN) is a new disease in Sub-Saharan Africa (SSA) caused by double infection by maize chlorotic mottle virus (MCMV) with any of the many viral agents in the Potyviridae family. It has become one of the key constraints to maize production in the region due to the significant crop losses caused since its emergence in 2011. Sustainable management of MLN is achievable through genetic improvement and replacement of old susceptible varieties with farmer-preferred varieties that combine MLN resistance with tolerance to other prevailing biotic and abiotic stresses. To effectively breed for MLN resistance, it is important to identify sources of resistance, determine the genetic nature of resistance and employ efficient breeding techniques that will result in high genetic gains from selection. This study aimed to dissect the genetic nature of MLN using elite and introduced inbred lines from tropical and temperate maize genetic pools, new biparental populations and potential hybrids. The genetic analysis was conducted in five studies representing the major stages of maize breeding, from pre-breeding to variety development. In the pre-breeding study, the breeding potential for MLN resistance among 18 tropical and temperate inbred and doubled haploid (DH) lines was conducted to identify the best parents for population development. The second study on the genetic potential and usefulness of new pedigree populations was conducted using nine segregating biparental populations derived by crossing susceptible elite and recycled DH lines to two introduced MLN resistant lines from the KS23 pool. The third study, using a section of these populations, selected three sizable populations, which were phenotyped, genotyped and used to validate quantitative trait loci (QTL) linked to MLN resistance in the KS23 genetic background. The fourth study, moving towards product development, entailed determining the potential of new lines and single crosses for use as MLN resistant testers and hybrid parents. In this study, the combining ability for MLN resistance and agronomic traits was estimated among tropical MLN resistant maize lines and prospective single cross testers. Finally, MLN-resistant three-way test cross hybrids (potential new varieties) were evaluated to determine the magnitude of genotype by environment interaction (GEI) and yield stability of hybrids under stress and optimum conditions. Results indicated overall high genetic variation for MLN resistance among introduced and adapted inbred lines, segregating populations and test cross hybrids. High heritability estimates were also observed among the diverse germplasm categories. With the high heritability estimates observed, significant gains from selection can be achieved for both MLN resistance and agronomic traits. The pre-breeding assessment identified good inbred lines suitable for formation of new MLN resistant populations. Testcross analysis led to identification of two resistant inbred lines and seven potential single cross testers that could be used for routine MLN resistance breeding. Multi-location experiments on three-way testcross hybrids identified 11 potential hybrids stable under MLN pressure and disease-free conditions. These hybrids could be further tested, released and commercialised. Genetic analysis and QTL mapping using biparental populations led to the validation of one major recessively inherited QTL located on the long arm of chromosome 6, consistently linked to three Kompetitive allele-specific polymerase chain reaction (KASP) markers across three mapping populations. This major candidate QTL needs to be fine-mapped and high-quality markers linked to the QTL selected and used for routine MLN resistance breeding in SSA and globally.
Thesis (Ph.D. (Plant Sciences))--University of the Free State, 2021
Keywords: MLN resistance; Pre-breeding; Usefulness criterion; Combining ability; QTL mapping; Linkage analysis; Genotype x environment interaction and stability